The librarian's guide to negotiation [ winning strategies for the digital age - Ashmore, Beth , 1976-; Grogg, Jill E. , 1972-; Weddle, Jeff (Information Today, 2012)
Librarians negotiate every day with vendors, funding agencies, administrators, employees, co-workers, and patrons-yet the art of negotiation receives little attention in library education and training. This practical guide by three experienced librarian-negotiators will help you develop the mindset, skills, and confidence you need to negotiate effectively in any situation. The authors provide an in-depth look at negotiation in theory and practice, share tactics and strategies of top negotiators, offer techniques for overcoming emotional responses to conflict, recall successful outcomes and deals gone awry, and demonstrate the importance of negotiating expertise to libraries and library careers. The result is an eye-opening survey into the true nature of negotiation-both as a form of communication and as a tool you can use to create sustainable collections and improve library service in the digital age